Etnobotani Buah Edibel Pada Masyarakat Dayak Tahol Di Kabupaten Malinau, Kalimantan Utara - Ardiansyah, DT; Hendra, Medi; Susanto, Dwi (BIOPROSPEK: Jurnal Ilmiah Biologi, 2018)
Forest has been considered as one of natural resources that could brought benefits for Dayak community based on their ecological and economical values. Edible fruits are annual plant type that could grow fruits and can be consumed. This study was held to obtain data, what type of plant that is utilized by Dayak Tahol community in their daily lives and how they utilize the edible fruits from Malinau district. This study was conducted by using explorative survey method, which is divided into two steps: first, the edible fruits inventory which is familiar by local people; second, observation at the local community and this method is supported by approach and sampling technique. This result showed that the total known edible fruits plant was about fifty two genus obtained from twenty five families and 2.207 individual species in total, moreover Shanoon-Winner diversity index (H’= 3.49) can be grouped in high diversity (H’ > 3).